Investigating the Relationship between Will Power and Spiritual Well-Being among Students: A Structural Equation Model - Amerian 1, Mohammadreza; Kohsari 2*, Reza; Saberyan 3, Alireza (Shahroud Journal of Medical Sciences, 2019)
Backgrounds: Spiritual health is one of the important health dimensions, which helps stabilizing the person's internal characteristics and improves the individuals' quality of life. The aim of the study was to investigate the relationship between will-power and spiritual well-being of students in Shahroud University of Medical Sciences. Methods: 431 students were evaluated by distributing the Paloutzian and Ellison Spiritual well-being Questionnaire and Iranian Will-Power Inventory. Spiritual health as a dependent variable, and power of will and the variables of gender, age, marital status, field of study, place of residence, and being native or non-native were measured. Results: Regression results of structural equations showed that the demographic factors such as gender, marital status, educational level, and will-power variables predict the spiritual health score belonged to the students. The results also indicated that the will-power is associated with an increase in the spiritual health score of the students (beta=0.61, Pvalue=0.001). Conclusions: Based on the findings, it seems that through the educational interventions and presentation of educational packages, strengthening of will-power is necessary for promoting the spiritual health of the students. Keywords: Spiritual Well-Being, Will-Power, Students, Structural Equation Model